Alpha1-Adrenergic Receptor Activation Stimulates Calcium Entry and Proliferation via TRPC6 Channels in Cultured Human Mesangial Cells - Fanwu Kong; Linlin Ma; Li Zou; Kexin Meng; Tianrong Ji; Lei Zhang; Rui Zhang; Jundong Jiao (Cellular Physiology and Biochemistry, 2015)
Background and Aims: There is accumulating evidence that sympathetic nervous hyperactivity contributes to the pathogenesis of glomerular sclerosis independent of blood pressure effects. A previous study showed that α1-adrenoceptor (α1-AR) antagonists inhibit mesangial cell (MC) proliferation. However, the underlying mechanism remains unclear. Methods and Results: We found that α1-AR is expressed in a human mesangial cell line. The α1-AR agonist phenylephrine (PE) induced Ca2+ influx as well as release from intracellular Ca2+ stores. Blockade of TRPC6 with siRNA, anti-TRPC6 antibodies and a TRPC blocker attenuated the PE-induced [Ca2+]i increase. Additionally, the PE-induced [Ca2+]i increase was phospholipase C dependent. Furthermore, PE induced a [Ca2+]i increase even when the intracellular Ca2+ stores were already depleted. This effect was mimicked by an analog of diacylglycerol. These results suggested that, upon α1-AR stimulation, TRPC6 mediates Ca2+ influx via a receptor-operated Ca2+ entry mechanism. Finally, TRPC6 contributes to the PE-induced MC proliferation. The mechanisms are associated with the extracellular signal-regulated kinase (ERK) signaling pathway because blockade of TRPC6 and chelation of extracellular Ca2+ abrogated PE-induced ERK1/2 abrogated PE-induced ERK1/2 phosphorylation. Conclusion: TRPC6 channels are involved in α1-AR activation-induced Ca2+ entry, which mediates proliferation via ERK signaling in human MCs